Formulasi Penetapan Besaran Pajak Lingkungan Hidup pada Perusahaan Pertambangan dalam Pengendalian Kerusakan Lingkungan Hidup: Suatu Pendekatan Literatur - Pandapotan, Daniel (Journal of Accounting and Investment, 2013)
One of company activies that relate directly to the environment is a mining activity. Tax can be instrument to control the environment, and also financing instrument to recover environment damage by mining activity. Therefore, Mining Companies are encouraged to manage environment information and report the enviromental costs to their stakeholders. This research uses a qualitatif approach because qualitatif research is more complex to give details of informations in difficult expressions. The design of this research is qualitative descriptive to develop the research idea. This reseacrh is based on secondary data such as literature review, government regulation about taxes and environment, and others reseacrh. In terms of analyzing the data, researcher conducted domain analysis to do exploration new idea. The researchÂ  results are to identify environmental costs in mining companies of its activities which consists of prevention costs, detection costs, internal failure costs, and external failure costs, to design environmental taxation mechanism and to determine the base of environmental tax.